Quand le jardin révèle un imaginaire du paysage méditerranéen : les Colombières de Ferdinand Bac - Agnès du Vachat (Projets de Paysage)
This article studies the role of the imagination, as the mental faculty for transforming reality, in the work of the landscape architect Ferdinand Bac (1859-1952) as well as his contribution to the imaginary Mediterranean landscape in the 20th century. In his major work, the Colombières garden in Menton in 1925, Bac applied his principles for the renewal of a Mediterranean art, by breaking with the trend of the pastiche and of exoticism which was then in vogue on the Côte d’Azur. Drawing inspiration from art, literature, and his travel experiences, he recreated in his garden landscape scenes evoking Ancient Greece, the Roman Empire, Spain under the Arabian and Catholic influences, and Renaissance Italy. By so doing, he contributed to enhancing the imaginary dimension of the Mediterranean landscape. The critical acclaim his garden received throughout Europe and beyond, made Bac the instigator of a new style in the garden arts, the Mediterranean garden.